Study on the size effect of the secant modulus of rocks containing multiple parallel joints - Zhang, Jing; Guo, Wannian; Fu, Yongzhi; Feng, Yong; Wang, Qingxia; Hu, Gaojian; Wang, Tao (Frontiers in Materials, 2022)
The secant modulus of rock reflects the stiffness of rock and the ability to resist deformation. There are significant differences in secant modulus of rock due to the different numbers of joints in rock and the change of rock size. Therefore, it is important to obtain effectively the secant modulus of rocks with the number of parallel joints for evaluating rock deformation. In this paper, the method of regression analysis is used, and 10 sets of numerical plans are set up to discuss the influence of number of parallel joints and rock size on the secant modulus. The results show that the secant modulus decreases with the increase of number of parallel joints, and the curve is a power function. The secant modulus decreases when rock size increases, and the curve is an exponential function. The characteristic secant modulus and characteristic size decreases with the increase of number of parallel joints, and their curves are an exponential function. The specific forms of these relationships are given in the article. The establishment of these relationships realizes the prediction and calculation of the rock secant modulus with the number of parallel joints, which provides a guiding significance for the rock deformation analysis.